An Integrative and Modular Framework to Recapitulate Emergent Behavior in Cell Migration - Cuenca, Marina B.; Canedo, Lucía; Perez-Castro, Carolina; Grecco, Hernan E. (Frontiers in Cell and Developmental Biology, 2020)
Cell migration has been a subject of study in a broad variety of biological systems, from morphogenetic events during development to cancer progression. In this work, we describe single-cell movement in a modular framework from which we simulated the collective behavior of glioblastoma (GBM) cells, the most prevalent and malignant primary brain tumor. Here, cells are spatially closely packed and organized in 3D structures and they migrate away from the colony in different patterns. Our integrative model considers the most relevant mechanisms involved in cell migration: chemotaxis of attractant factor, mechanical interactions and random movement. Our simulations fitted and reproduce the emergent behavior of the cell colonies in a set of migration assays where single-cell trajectories were tracked. We also predicted the effect of migration inhibition on the colonies from simple experimental characterization. The development of tools that allow complementing molecular knowledge in migratory cell behavior is relevant for understanding essential cellular processes, both physiological (such as organ formation, tissue regeneration among others) and pathological. Overall, this is a versatile tool that has proven to predict individual and collective behavior on GBM cells, but that can be applied to a broad variety of scenarios.